METAPHYSICAL FOUNDATION OF TRUTH: EXPLORING G.R. MALKANI’S PHILOSOPHICAL VISION IN THE CONTEXT OF INDIAN IDEALISM - Sarma, Deepamoni; Devi, Sabitri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Truth, as used in philosophy, is a universal and immutable reality and it has been the subject of independent discussion for millennia. The understanding of truth is the only thing that satisfies the ideal of philosophy. Philosophical knowledge, like any other knowledge, must be able to address questions. It is clear that philosophical thought is a type of theoretical endeavor. The goal of theoretical activity is to get some sort of knowledge. However, each species of knowledge is a response to questions. We can be asked a direct question or one that is merely implied. However, there can be no knowledge if there are no questions. Actually, the cognitive nature of all knowledge is derived from the fact that it is a response to a query. If we are unable to identify what question a statement in the indicative mood makes is meant to address, it makes sense. G.R. Malkani stated that the question of ‘truth’ is the central issue of theoretic consciousness. Philosophers are able to differentiate what is true and what is not, what is real and what is unreal. For him nothing is more valuable than truth in its purest light, indeed, Divinity itself. This truth is unchangeable and devoid of error. There is no ignorance of the essence of reality. We progressively ascend through error to ever-greater truth until we arrive at the truth that dispels all doubt and unities the knot in our hearts that keeps us as individuals striving for material goals through ignorance of the truth.